Simulation of novel process of CO2 conversion to liquid fuels. (January 2017) - Meiri, Nora; Radus, Roman; Herskowitz, Moti
Graphical abstract: Abstract: Carbon dioxide utilization by conversion with hydrogen into liquid fuels was simulated based on the experimental data of a novel process using CHEMCAD. A detailed kinetic model of the novel iron-based spinel catalyst that included reverse water gas shift (RWGS), Fischer-Tropsch synthesis (FTS), C5 + hydrocarbons and oxygenates, oligomerization of olefins, as well as hydrogenation of light olefins (C2 C4 ) was employed. The RWGS reaction rate was significantly inhibited by steam produced in the process because of the chemical equilibrium limitation and apparent strong adsorption. Therefore, periodical water removal is critical in the process, which required operation in several reactors in series or in a reactor with recycle. Those system configurations were examined and compared over a range of temperatures, pressures, weight hourly space velocities and carbon dioxide with hydrogen feed ratios. The other aspect of this process which has a significant impact on performance is the oligomerization of light olefins. Both reactors-in-series and single reactor with recycle improved dramatically the productivity and the selectivity to C5 +.